Reliability of histological malignancy grade, ER and HER2 status on core needle biopsy vs surgical specimen in breast cancer. Issue 9 (21st December 2013) - Munch‐Petersen, Helga D.; Rasmussen, Birgitte B.; Balslev, Eva
<x xml:space="preserve">Abstract</x> Early determination of malignancy grade and biomarkers in primary breast cancer is important when planning the treatment with neoadjuvant therapy and breast‐conserving surgery. The aim of this study was to assess the reliability of malignancy grade on core needle biopsies, and to compare the concordance of ER and HER2 status on core needle biopsies vs surgical specimens. Eighty‐nine patients with invasive ductal or lobular carcinoma were included. Malignancy grade was upgraded by one degree in 23.0%. The mitotic count had most impact on the malignancy grade, and may be underestimated on core needle biopsies compared with surgical specimens. ER status was concordant in core needle biopsies and surgical specimens in 98.0%, but should be repeated when doubtfully negative. HER2 status was concordant in 84.0% prior to FISH‐HER2. Including FISH‐HER2 data, the core needle biopsies showed a final total concordance of 95.4%. In conclusion, ER and HER2 are useful markers in core needle biopsies, providing a reliable base for preoperative decisions in neoadjuvant chemotherapy, and may be omitted on surgical specimens with certain precautions and exceptions. Determination of malignancy grade should be repeated on surgical specimens, and one should be aware of underestimation on core needle biopsies.